Efficient CdS/CdSe/ZnS quantum dot sensitized solar cells prepared by ZnS treatment from methanol solvent. (1st March 2017) - Samadpour, M.
Highlights: ZnS treatment from methanol solvent is introduced for efficiency enhancement in QDSSCs. Efficiency is improved from 2.43% to 4.23% by ZnS treatment from methanolic precursor. We show that ZnS enhance the recombination resistance while conduction band is not affected. Abstract: Here a systematic study is performed on the effect of ZnS treatment on quantum dot (QD) sensitized photoanodes from alcoholic precursors. We show that the efficiency of quantum dot sensitized solar cells (QDSCs) can simply improve by replacing convenient aqueous precursors with methanolic ones during ZnS deposition using the successive ionic layer adsorption and reaction (SILAR) method. The open circuit voltage of the cells was increased more than 60 mv and their efficiency was improved more than 70% by a simple ZnS treatment of the CdS/CdSe sensitized photoanodes. We explain that ZnS methanolic precursors, compared to aqueous ones, can diffuse deeper into the mesoporous CdS/CdSe sensitized TiO2 anode. The efficiency of CdS/CdSe sensitized cells was increased from 2.43% (Voc  = 544 mV, Jsc  = 10.5 mA/cm 2, FF = 0.42) to 4.23% (Voc  = 612 mV, Jsc  = 13.3 mA/cm 2, FF = 0.52) by a simple ZnS treatment. A comprehensive study is carried out on the effect of the ZnS treatment on QDSCs performance by diffuse reflectance spectroscopy (DRS), impedance spectroscopy (IS), and applied bias voltage decay (ABVD) methods. Our results confirm that enhancing the recombination resistance is clearly one of the most important roles of the ZnS treatment. We show that, in spite of the enhanced open circuit voltage, the TiO2 conduction band is not shifted by the ZnS treatment. The results also demonstrate that ZnS deposition from low surface tension solutions can be systematically applied to enhance the performance of QDSCs.